2009
DOI: 10.1523/jneurosci.5256-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide S Reinstates Cocaine-Seeking Behavior and Increases Locomotor Activity through Corticotropin-Releasing Factor Receptor 1 in Mice

Abstract: Neuropeptide S (NPS) is a recently discovered neuropeptide that increases arousal and wakefulness while decreasing anxiety-like behavior. Here, we used a self-administration paradigm to demonstrate that intracerebroventricular infusion of NPS reinstates extinguished cocaine-seeking behavior in a dose-dependent manner in mice. The highest dose of NPS (0.45 nM) increased active lever pressing in the absence of cocaine to levels that were equivalent to those observed during self-administration. In addition, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 35 publications
6
95
0
Order By: Relevance
“…1,2 Recent evidence from rodent models indicates that the NPS system is critically involved in the regulation of unconditioned and conditioned fear behaviors. 1,[3][4][5][6][7] In humans, the locus for the NPS receptor gene NPSR1 maps to a chromosomal region that has reproducibly been linked to PD, with those markers creating the highest lod scores lying in close vicinity to he NPSR1 locus. [8][9][10] NPSR1 contains a frequent A>T polymorphism (rs324981) that codes for an Asn/Ile change at position 107.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent evidence from rodent models indicates that the NPS system is critically involved in the regulation of unconditioned and conditioned fear behaviors. 1,[3][4][5][6][7] In humans, the locus for the NPS receptor gene NPSR1 maps to a chromosomal region that has reproducibly been linked to PD, with those markers creating the highest lod scores lying in close vicinity to he NPSR1 locus. [8][9][10] NPSR1 contains a frequent A>T polymorphism (rs324981) that codes for an Asn/Ile change at position 107.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Pañeda and coworkers reported that ICV NPS itself increased relapse-like behavior in mice previously trained to self-administer cocaine. This latter effect was blocked by CRF1R antagonism and was absent in CRF1 receptor KO mice, suggesting a stress-like effect of NPS under the experimental conditions used (5).…”
mentioning
confidence: 85%
“…In this respect, it would be highly interesting to study the possible link between the NPS system, alcohol withdrawal, and anxiety, given that on the one hand, NPS is related to anxiolytic-like actions (Leonard et al, 2008;Vitale et al, 2008), while on the other, it activates the HPA axis and increases relapse to alcohol and cocaine seeking elicited by conditioning factors and drug priming, respectively (Cannella et al, 2009;Paneda et al, 2009). …”
Section: N Europeptide S (Nps) Is the Recently Discovered Endogenousmentioning
confidence: 99%